2007
DOI: 10.1002/art.22996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical training on the proportion of slow‐twitch type I muscle fibers, a novel nonimmune‐mediated mechanism for muscle impairment in polymyositis or dermatomyositis

Abstract: Objective. To compare muscle fiber type composition and muscle fiber area in patients with chronic polymyositis or dermatomyositis and healthy controls, and to determine whether physical training for 12 weeks could alter these muscle characteristics. Methods. Muscle fiber type composition and muscle fiber area were investigated by biochemical and immunohistochemistry techniques in repeated muscle biopsy samples obtained from 9 patients with chronic myositis before and after a 12-week exercise program and in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 46 publications
9
59
0
9
Order By: Relevance
“…Further support is provided by the low percentage of type I, oxygendependent, muscle fibers in patients with chronic polymyositis or dermato myositis, together with improved muscle endurance and an increased percentage of type I fibers after a 12week submaximal home exercise program. 78 Moreover, after a 7week intensive resistance training program, the levels of 265 gene transcripts were substantially modified in muscle tissue of patients with myositis, and seven of them showed a shift towards altered expression of enzymes involved with oxidative metabolism. 79 Hypoxia might induce muscle weakness by a number of pathways.…”
Section: Hypoxiamentioning
confidence: 99%
“…Further support is provided by the low percentage of type I, oxygendependent, muscle fibers in patients with chronic polymyositis or dermato myositis, together with improved muscle endurance and an increased percentage of type I fibers after a 12week submaximal home exercise program. 78 Moreover, after a 7week intensive resistance training program, the levels of 265 gene transcripts were substantially modified in muscle tissue of patients with myositis, and seven of them showed a shift towards altered expression of enzymes involved with oxidative metabolism. 79 Hypoxia might induce muscle weakness by a number of pathways.…”
Section: Hypoxiamentioning
confidence: 99%
“…[91][92][93][94][95][96][97][98][99] Importantly, a number of studies have found an association of these effects with improve ments in selfreported fatigue and healthrelated quality of life. 77 Box 1 | Exercise is medicine-rheumatoid arthritis Improved physical capacity ■ Increased muscle strength and functional ability in response to resistance 76,114 and resistance plus aerobic exercise programmes [73][74][75]115,[120][121][122]126 ■ Increased aerobic capacity in response to aerobic 72 and resistance plus aerobic exercise programmes [73][74][75]115,121 ■ Decreased self-reported fatigue and self-reported quality of life in response to aerobic plus resistance exercise programmes, 100 and shown by cross-sectional studies 77,100 Improved body composition ■ Increased muscle mass in response to resistance 76,114,116 and resistance plus aerobic exercise programmes 113,115 ■ Decreased total and upper-body fat mass in response to resistance 76,116 and resistance plus aerobic exercise programmes [73][74][75]115 Improved cardiovascular function ■ Improved endothelial function, blood pressure, lipid profile, and insulin resistance in response to resistance plus aerobic exercise programmes 75,102,105 ■ Improved autonomic function in response to resistance plus aerobic exercise programmes 107…”
Section: Physical Capacity and Functional Improvementsmentioning
confidence: 99%
“…[87][88][89][90] Moreover, studies have reported no increases in muscle inflammation or damage after resistance exercise training programmes by patients with idiopathic inflammatory myopathy. 93,94,98 Although preliminary, evidence exists that exercise does not exacerbate systemic inflammation, particu larly in patients with RA, SLE or idiopathic inflamma tory myopathy. Baslund et al 72 found, in patients with RA, that 8 weeks of moderate intensity aerobic training did not affect a number of resting immune parameters, including circulating concentrations of IL1α, IL1β and Box 3 | Exercise is medicine-inflammatory myopathies Improved physical capacity ■ Increased muscle strength and function in response to aerobic 96 and resistance exercise programmes 93-95,97,98,151 ■ Increased aerobic capacity in response to aerobic 96 and resistance exercise programmes 94 …”
Section: Effects On Inflammationmentioning
confidence: 99%
“…This observation together with clinical symptoms of muscle fatigue and low levels of ATP and phosphocreatine in muscle tissue assessed by MR spectroscopy could indicate a hypoxic status in skeletal muscle [10]. The hypoxia hypothesis is further supported by the beneficial clinical effects of endurance exercise together with an increased ratio of oxidative type I fibers noted in repeat muscle biopsies taken before and after an exercise period of 12 weeks [11].…”
Section: Exercise In Inflammatory Myopathiesmentioning
confidence: 76%
“…In another chronic condition such as chronic heart failure, in which subclinical inflammation may be present, exercise training reduced serum levels of tumor necrosis factor (TNF) and exercise-dependent reduction in plasma levels of IL-6 was recorded in men with type 2 diabetes [16]. Similarly, in myositis, in which infiltration of skeletal muscle by inflammatory cells is a key feature of disease, exercise interventions can favorably modulate health outcomes [5,6,11,17]. Despite this important evidence, current guidelines for exercise prescription for patients with chronic inflammatory disorders are ill defined.…”
Section: Anti-inflammatory Effects Of Exercisementioning
confidence: 99%